MISCELLANEOUS NOTES ON MAINLY SOUTHEAST ASIANGRAMINEAE - Veldkamp, Jan Frits (REINWARDTIA, 2004)
VELDKAMP, J.F. 2004. Miscellaneous notes on mainly Southeast Asian Gramineae. Reinwardtia 12(2): 135 â140. â During the preparation of a revision of the herbaceous grasses of SE Asia a few nomenclatural and taxonomic novelties were detected. New combinations are proposed in Aristida L., Kengia Packer, Rytidosperma Steud., and Urochloa P. Beauv. Aristida novaeguineae Ohwi is re-instated as a distinct species. A key to the Malesian species of Aristida L. is provided. Moorochloa Veldk. replaces Brachiaria auct., s.s.